Avian urban ecology in Nepal: A call for attention - Bhusal, Dinesh; Ghimire, Prashant (Nepalese Journal of Zoology, 2023)
Urbanization is increasing at an unprecedented rate, leading to changes in land use resulting in the loss of habitat for birds worldwide. Nevertheless, urban areas still support approximately 20% of the world's bird population. In Nepal, urbanization has been rapidly increasing in recent decades, yet little attention has been paid to urban biodiversity exacerbating the impact of urban expansion on threatened birds. In this perspective article, we explore studies on urban birds in Nepal to identify existing research patterns, discuss what has been known, outline gaps and pave immediate future interventions in studies of avian urban ecology in Nepal. There has been a significantly lower number of studies on urban birds in Nepal compared to neighbouring India and China in the last 10 years. Studies of urban birds in Nepal are at a very early stage focused on the diversity and richness in Kathmandu, Pokhara and Butwal with no baseline data for other major cities. Our understanding of bird homogenization or extinction as well as the effects of birds on cities, such as their rapid colonization and potential role as pests, may be limited by this dearth of knowledge about urban birds and biodiversity. Therefore, we have outlined future research opportunities in avian urban ecology in Nepal such as long-term bird surveys, interdisciplinary field of studies, diseases study, management of urban green spaces, avian adaptation to urban environments, colonization and extinction patterns in cities, and conflicts, challenges, and management strategies related to urban avian ecology. With this article, we call the immediate attention of scientists, urban planners, and related stakeholders to use birds as a model system to study urban environments which could be a good start in building a bird-friendly city.